(untitled) (Zaporizhzhia Historical Review, 2021)
The article touches upon the problems of the French-Ukrainian bilateral computer terms translation. Nowadays many computer terms are adopted from English directly or via Russian. Besides, there is no Ukrainian standard term system and, as a result, French-Ukrainian dictionaries of computer science. This all is crucial problem for our French-Ukrainian translators who have to do a double translation via English or Russian.